Pregnancy Outcome After Methotrexate Treatment for Rheumatic Disease Prior to or During Early Pregnancy: A Prospective Multicenter Cohort Study. Issue 5 (May 2014) - Weber‐Schoendorfer, Corinna; Chambers, Christina; Wacker, Evelin; Beghin, Delphine; Bernard, Nathalie; ,; Shechtman, Svetlana; Johnson, Diana; Cuppers‐Maarschalkerweerd, Benedikte; Pistelli, Alessandra; Clementi, Maurizio; Winterfeld, Ursula; et al.
<x xml:space="preserve">Abstract</x> Objective High‐dose methotrexate (MTX) exposure during pregnancy is associated with embryopathy. The teratogenic potential of MTX at dosages typically used in the treatment of rheumatic diseases remains uncertain. The aim of this study was to evaluate the risk of spontaneous abortion, major birth defects, elective termination of pregnancy, shortened gestational age at delivery, and reduced birth weight in women exposed to MTX. Methods Pregnancy outcome in women taking MTX (≤30 mg/week) either after conception or within the 12 weeks before conception was evaluated in a prospective observational multicenter cohort study. Pregnancy outcomes in the MTX group were compared to outcomes in a group of disease‐matched women and a group of women without autoimmune diseases (neither group was exposed to MTX). Results The study sample included 324 MTX‐exposed pregnancies (188 exposed post‐conception, 136 exposed pre‐conception), 459 disease‐matched comparison women, and 1, 107 comparison women without autoimmune diseases. In the post‐conception cohort, the cumulative incidence of spontaneous abortion was 42.5% (95% confidence interval [95% CI] 29.2–58.7), which was significantly higher than the incidence of spontaneous abortion in either comparison group. The risk of major birth defects (7 of 106 [6.6%]) was elevated compared to both the cohort of women without autoimmune diseases (29 of 1, 001 [2.9%]) (adjusted odds ratio [OR] 3.1 [95% CI 1.03–9.5]) and the disease‐matched cohort (14 of 393 [3.6%]) (adjusted OR 1.8 [95% CI 0.6–5.7]). None of the malformations were clearly consistent with MTX embryopathy. Neither the cumulative incidence of spontaneous abortion (14.4% [95% CI 8.0–25.3]) nor the risk of major birth defects (4 of 114 [3.5%]) was increased in the pre‐conception cohort. Elective termination rates were increased in both of the MTX‐exposed cohorts. There were no other significant differences among groups in other study end points. Conclusion Post‐conception administration of MTX at dosages typically used in the treatment of rheumatic diseases was associated with an increased risk of major birth defects and spontaneous abortion. Such evidence was not found among women in our pre‐conception cohort.